PENGARUH LATIHAN E-MOVEMENT CONE DRILL TERHADAP KELINCAHAN PADA PEMAIN U-17 SSB BAGOGA KECAMATAN KUBU BABUSSALAM KABUPATEN ROKAN HILIR - Suprizal, Suprizal; Slamet, Slamet; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The problem in this research is there was tendency of being turning of the players, the slower of the player in distracting the opponent's movement team when they controlled the ball, the difficulty of the player in grabbing the ball from the opponent team hence they often fell without any body contact while chasing the ball. Based on these problems the researcher gave the exercise of E-Movement Cone Drill for 16 meetings. This study aimed to determine whether there was influence of E-Movement Cone Drill exercise toward the Agility of the players, so the players were able to maximize in playing the ball agility . The form of this study was aexperiment research(Experiment),with the population of u-17 SSB Bagoga Players of Kubu Babu ssalam Rokan Hilir Regency, the data in this study was the entire population which consisted of 16 players. The instrument of this research is Illinois Agility Test which aimed to measure Agility of SSB Players Bagoga. After that, the data were sampled with statistics, to test the normality with the lilifors test at a significant level of α ( 0.05 ). The hypothesis proposed whether there was an influence of E-Movement Cone Drill Exercises for Agility on U-17 SSB Bagoga Player districts Kubu Babussalam of Rokan Hilir Regency. Based on statistical data analysis, there is an average pre-test of 1 8,06 and the average post-test of 17.61, then the data is normal with an increase value difference (d) an average of 0.46. Based on t test analysis yield T count 15,3 and Ttable 1,75 it means Tcount >T table. Thus, there is an Effect of Exercise E-Movement against Agility Cone Drill on U17 SSB Bagoga Player of Kubu Babu salam district of Rokan Hilir Regency.Keywords : E-Movement Cone Drill , The Agility